2020
DOI: 10.3389/fmicb.2019.02928
|View full text |Cite
|
Sign up to set email alerts
|

Mygalin: An Acylpolyamine With Bactericidal Activity

Abstract: Inappropriate use of antibiotics favors the selection and spread of resistant bacteria. To reduce the spread of these bacteria, finding new molecules with activity is urgent and necessary. Several polyamine analogs have been constructed and used to control microorganisms and tumor cells. Mygalin is a synthetic acylpolyamine, which are analogs of spermidine, derived from the hemolymph of the spider Acanthoscurria gomesiana. The effective activity of polyamines and their analogs has been associated with their st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 67 publications
1
15
1
Order By: Relevance
“…Mygalin was subjected to multiple tests to elucidate the mechanisms responsible for the antimicrobial activity against E. coli. In a viability assay, mygalin (0.5 mM) was more effective than H 2 O 2 (1 mM) [28]. Alkaline electrophoresis gel showed that mygalin causes oxidative DNA damage, which was also observed in E. coli model by confocal microscopy.…”
Section: Acanthoscurria Gomesianamentioning
confidence: 80%
See 1 more Smart Citation
“…Mygalin was subjected to multiple tests to elucidate the mechanisms responsible for the antimicrobial activity against E. coli. In a viability assay, mygalin (0.5 mM) was more effective than H 2 O 2 (1 mM) [28]. Alkaline electrophoresis gel showed that mygalin causes oxidative DNA damage, which was also observed in E. coli model by confocal microscopy.…”
Section: Acanthoscurria Gomesianamentioning
confidence: 80%
“…DAPI is a fluorescent dye that intercalates with DNA double-helix and is commonly used to evaluate structural damage on DNA. Filamentation assay with 10 6 CFU/mL treated with 0.5 mM for 3h revealed the capacity of mygalin to interfere on cell division by binding to DNA, causing inhibition of its synthesis in vivo [28].…”
Section: Acanthoscurria Gomesianamentioning
confidence: 99%
“…The compound mygalin used in this study is a diacylspermidine synthesized from an analogous molecule present in the hemolymph of the spider Acanthoscurria gomesiana (Araneae, Theraphosidae; Graphical Abstract). [10] Although mygalin is not an acyl-polyamine, the chemical structure of synthesized diacylpespermidine is similar to the natural (n = 9 rats per group). ANOVA, analysis of variance acyl-polyamines.…”
Section: Discussionmentioning
confidence: 94%
“…Mygalin was diluted into Milli-Q deionized water-vehicle (Millipore); LY 235959, MK-801, and morphine were diluted into saline; CNQX and NBQX were diluted into dimethyl sulfoxide (all from Sigma-Aldrich). Mygalin (>98% purity; Supporting Information) was synthesized at the Centre for Research on Toxins, Immune-Response and Cell Signaling (CeTICS-CEPID), Laboratory for Applied Toxinology-Butantan Institute, and provided by Dr. Pedro Ismael da Silva Jr. As described by Espinoza-Culupú et al, [10] the guidelines for the synthesis followed a classical method of peptide chemistry. [23] The synthesis was carried out in 2-(1H-benzotriazol-1-yl)−1,1,3,3tetramethyluronium hexafluorophosphate solution [24] for the esterification of the carboxyl group of gentisic acid and thus permitting the formation of one carboxamide by formal condensation of two primary amino groups from spermidine with a carboxylic group of two molecules of gentisic acid (2,5-dihydroxybenzoic acid).…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation